Perception and Practices of Teaching Grammar in Higher Secondary Schools in Bhutan. - Nima Wangchuk; Chencho Wangchuk; Dhanapati Sharma; Phub Dorji (Journal of English as A Foreign Language Teaching and Research, 2021)
This paper reports a survey of Bhutanese teachers’ Perception and Practices of Teaching Grammar in Higher Secondary Schools in Bhutan. The teaching of grammar in Bhutanese school is predominately guided by curriculum, whereby context-based teaching is mostly encouraged. The descriptive analysis based on quantitative findings of the study indicated that Bhutanese teachers generally believed that the formal study of grammar is essential to the eventual mastery of a foreign or second language.  The study also showed that grammar is generally believed to be best taught explicitly, inductively or deductively, but not implicitly. Moreover, the teachers' remark on the importance of systematic practice of grammatical features and detailed error correction suggests that there is a preference for more extensive treatment of grammatical issues.  The findings of the present study also indicate that, like the teachers reported in the 2002 and 2008 studies, teachers in Bhutan appreciate the centrality of grammar in their language teaching. This descriptive analysis based on quantitative findings would be beneficial to the curriculum developers, teachers, and lecturers in developing students’ grammar skills and providing professional development to teachers for effective delivery of grammar lessons